SLB Connect for Urban Water Supply and Sanitation : Using ICTs for Citizen Feedback Surveys to Mainstream Demand-side Monitoring - Bhatnagar, Vandana (World Bank, Washington, DC, 2017)
SLB Connect is an initiative of the World Bank’s Water and Sanitation Program, developed inpartnership with India’s Ministry of Urban Development (MoUD), to complement the Ministry’s ServiceLevel Benchmarks (SLB) program. Under the SLB program, providers of water supply, wastewater, solidwaste management and storm-water drainage services report data on a standardized set of 28 performance indicators. Grants to municipalities have been linked to reporting on these indicators, and, over time, SLB data have become an integral component of India’s urban programformulations. SLB Connect complements SLB data by gathering feedback from the citizens who use those services. The demand-side data are intended to improve tracking of service outcomes,provide a reality check for supply-side data reported by providers, identify problems with serviceoutcomes at local (ward/zone) level, identify inequities by user groups (for example, households in slum settlements), and ultimately improve service providers’ accountability to citizens. The SLB Connect program leverages the use of Information and Communication Technologies (ICTs) for collecting feedback, which fits with the Government of India’s broader interest in using ICTs to strengthen citizen engagement for improving service delivery, including through the development of the National e-Governance Plan. As ICTs continue to develop, there will be increasing opportunities to make processes for gathering citizen feedback more intelligent, inclusive and efficient – and thereby leverage its use in decision making for improving service outcomes.